2023
DOI: 10.1186/s12935-023-02872-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of LncRNAs in tumor immunotherapy

Abstract: Cancer immunotherapy is a major breakthrough in the history of tumor therapy in the last decade. Immune checkpoint inhibitors blocking CTLA-4/B7 or PD-1/PD-L1 pathways have greatly prolonged the survival of patients with different cancers. Long non-coding RNAs (lncRNAs) are abnormally expressed in tumors and play an important role in tumor immunotherapy through immune regulation and immunotherapy resistance. In this review, we summarized the mechanisms of lncRNAs in regulating gene expression and well-studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 129 publications
0
13
0
Order By: Relevance
“…LncRNAs are recently gaining more attention in cancer research due to their high versatility in regulating gene expression. Many studies have already shown the role of lncRNAs in cancer hallmarks, and over the past years, the literature on the relation between lncRNAs and tumor immune response has grown significantly [27][28][29][30][31].…”
Section: Lncrnas and Immune Response: The Pd-1/pd-l1 Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are recently gaining more attention in cancer research due to their high versatility in regulating gene expression. Many studies have already shown the role of lncRNAs in cancer hallmarks, and over the past years, the literature on the relation between lncRNAs and tumor immune response has grown significantly [27][28][29][30][31].…”
Section: Lncrnas and Immune Response: The Pd-1/pd-l1 Pathwaymentioning
confidence: 99%
“…An integrative analysis of lncRNAs associated with tumor immune response including over 9000 samples across 32 cancer types was able to define a score (LIMER-lincRNA-based immune response) able to predict immune cell infiltration and prognosis [31]. In the same study, the authors described that lincRNA EPIC1 (epigenetically induced lincRNA-1) interacts with the histone methyltransferase EZH2, leading to the epigenetic silencing of several genes, including MHC-I genes, representing a possible mechanism of tumor immune evasion and, thus, resistance to immunotherapy.…”
Section: Lncrnas and Pd-1/pdl-1 Axis In Other Cancer Typesmentioning
confidence: 99%
“…Recent studies highlight the unique epigenetic landscape exhibited by exhausted T cells. Long non-coding RNA (lncRNA) and microRNA (miRNA) have emerged as key players regulating various biological functions, including T-cell activation, development, and differentiation. DNA methylation, a crucial epigenetic modification, is another essential regulatory factor significantly affecting gene expression in various cellular processes . The availability of comprehensive epigenetic data has opened new avenues for investigating TEX holistically.…”
Section: Introductionmentioning
confidence: 99%
“…According to other studies, HOTAIR functions as a trans-acting lncRNA and is linked to stomach cancer. According to a publication, overexpression of HOTAIR may encourage the growth of cancer cells in tissues by causing metastasis to spread to additional sites and organs [ 25 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%